2018
DOI: 10.1016/j.biopha.2018.08.131
|View full text |Cite
|
Sign up to set email alerts
|

Possible therapeutic potential of berberine in the treatment of STZ plus HFD-induced diabetic osteoporosis

Abstract: Diabetic osteoporosis is a complication of diabetes mellitus, and can result in an increased incidence of bone fractures and a delay in fracture healing. Berberine is one of the most widely distributed isoquinoline alkaloid in plants and possesses antioxidant properties. These properties can reduce the high glucose mediated in the dysfunction of human bone marrow stem cells. Therefore, the present study was designed to investigate the apparent beneficial effect of berberine on bone characteristics in streptozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 36 publications
3
26
2
Order By: Relevance
“…234 Berberine showed good effects on bone parameters in the treatment of HFD-fed/ streptozocin-induced diabetic rats and, thus, could have therapeutic potential in diabetic osteoporosis. 235…”
Section: Effect On Diabetes and Its Complicationsmentioning
confidence: 99%
“…234 Berberine showed good effects on bone parameters in the treatment of HFD-fed/ streptozocin-induced diabetic rats and, thus, could have therapeutic potential in diabetic osteoporosis. 235…”
Section: Effect On Diabetes and Its Complicationsmentioning
confidence: 99%
“…12 BBR has shown protective effects against bone loss, and restored decreased bone formation in diabetic and postmenopausal osteoporosis. [13][14][15][16] In addition, BBR promoted osteoblast differentiation and new bone area formation. 17 Moreover, BBR also activated the canonical Wnt/β-catenin pathway in bone marrow mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, recent researches have showed that CR has anti-bacterial [ 14 ], anti-cancer [ 15 ] activities, etc. Especially, berberine has been shown to possess remarkable effects on lowering blood glucose and promoting the secretion of insulin [ 16 , 17 ]. In China, SR and CR are often used together at a ratio of 1:1 to obtain a synergistic effect for treating diabetes and its complications, yet the underlying mechanism on the therapy of T2DM remains unclear.…”
Section: Introductionmentioning
confidence: 99%